Peranan Sistem Erp dan Perubahan Pola Kerja sebagai Upaya Meningkatkan Kinerja Perusahaan - Alianto, Hendra; Wijaya, Santo F (Bina Nusantara University, 2014)
The ERP system is an integrated system that supports the core business activities of a company. These activities include manufacturing, logistics, finance and accounting, sales and marketing, and human resources. The ERP system will help related departments in a company to share data and information, cost reduction, and improved management of business processes, which will have an impact on work activities become more efficient and more effective. The method in this research is a case study approach, analysis, evaluation of documents and data collection. This study aims to discuss how the role of the ERP system and changes in work patterns as an effort to improve the performance of companies backed by the role of the ERP system.